2012
DOI: 10.1177/1758736012456543
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar ridge resorption after tooth extraction: A consequence of a fundamental principle of bone physiology

Abstract: It is well established that tooth extraction is followed by a reduction of the buccolingual as well as the apicocoronal dimension of the alveolar ridge. Different measures have been taken to avoid this bone modelling process, such as immediate implant placement and bone grafting, but in most cases with disappointing results. One fundamental principle of bone physiology is the adaptation of bone mass and bone structure to the levels and frequencies of strain. In the present article, it is shown that the reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 36 publications
0
95
1
3
Order By: Relevance
“…Since the existence of alveolar bone is mutually connected to the dentition and other periodontal tissues, the alveolar ridge continues to resorb following tooth removal even if a dental implant is placed into a fresh extraction socket. Physiologically, this is caused by continuous bone remodeling in response to mechanical loading changes that occur with alterations in the applied force and strain distribution to the osseous tissue during mastication, as stipulated by Wolff's Law [2]. Ridge or socket preservation and augmentation using bone grafting materials is a clinically viable approach to maintain any remaining bone following tooth extraction and further condition it in preparation for dental implant placement.…”
Section: Introductionmentioning
confidence: 99%
“…Since the existence of alveolar bone is mutually connected to the dentition and other periodontal tissues, the alveolar ridge continues to resorb following tooth removal even if a dental implant is placed into a fresh extraction socket. Physiologically, this is caused by continuous bone remodeling in response to mechanical loading changes that occur with alterations in the applied force and strain distribution to the osseous tissue during mastication, as stipulated by Wolff's Law [2]. Ridge or socket preservation and augmentation using bone grafting materials is a clinically viable approach to maintain any remaining bone following tooth extraction and further condition it in preparation for dental implant placement.…”
Section: Introductionmentioning
confidence: 99%
“…Individual differences are observed in mandibular bone resorption, and the extent of absorption also varies by site, even in the mandible. Changes are particularly notable in the alveolar area, where reductions are seen in alveolar height and width 3) . Studies analyzing the bone structure of dentulous and edentulous mandibles showed significant differences between the two in bone mineral density (BMD) 4) , and studies are being carried out to explain the role of the load incurred via the teeth in changes in the internal structure of the mandible 5,6) .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have 9 looked at the rate at which this alveolar resorption occurs. In some dog studies, full alveolar remodeling is complete after 6 months (Cardaropoli et al, 2003) but some human experimental studies have noted that no examples of complete remodeling had occurred after 12 months of post-extraction monitoring of patients (Hansson and Halldin, 2012). A recent study by Morgan (2012) found that it takes at least 29 weeks in humans for sockets to be fully healed, which was defined on the basis of bone presence throughout the cavity left by tooth extraction (Morgan, 2011).…”
Section: Methodsmentioning
confidence: 99%